Talar and Subtalar T1ρ Relaxation Times in Limbs with and without Chronic Ankle Instability. (December 2021) - Song, Kyeongtak; Pietrosimone, Brian; Tennant, Joshua N.; Nissman, Daniel B.; Dederer, Katherine M.; Paranjape, Chinmay; Wikstrom, Erik A.
Objective: The primary aim was to determine differences in talocrural and subtalar joint (STJ) articular cartilage composition, using T1ρ magnetic resonance imaging (MRI) relaxation times, between limbs in individuals with unilateral chronic ankle instability (CAI) and compare with an uninjured control. Our secondary purpose was to determine the association between talocrural and STJ composition in limbs with and without CAI. Design: T1ρ MRI relaxation times were collected on 15 CAI (11 females, 21.13 ± 1.81 years, body mass index [BMI] = 23.96 ± 2.74 kg/m 2 ) and 15 uninjured control individuals (11 females, 21.07 ± 2.55 years, BMI = 24.59 ± 3.44 kg/m 2 ). Talocrural cartilage was segmented manually to identify the overall talar dome. The SJT cartilage was segmented manually to identify the anterior, medial, and posterior regions of interest consistent with STJ anatomical articulations. For each segmented area, a T1ρ relaxation time mean and variability value was calculated. Greater T1ρ relaxation times were interpreted as decreased proteoglycan content. Results: Individuals with CAI demonstrated a higher involved limb talocrural T1ρ mean and variability relative to their contralateral limb ( P < 0.05) and the healthy control limb ( P < 0.05). The CAI-involved limb also had a higher posterior STJ T1ρ mean relative to the healthy control limb ( P < 0.05). In healthy controls ( P < 0.05), but not the CAI-involved or contralateral limbs (p>0.05), talocrural and posterior STJ composition measures were positively associated. Conclusions: Individuals with CAI have lower proteoglycan content in both the talocrural and posterior STJ in their involved limbs relative to the contralateral and a healthy control limb. Cartilage composition findings may be consistent with the early development of posttraumatic osteoarthritis.